Analysis of the Characteristics of Ovarian Tumors - Siti Mirhalina (The International Science of Health Journal, 2023)
Ovarian tumor is a condition where the ovaries experience abnormal growth, disrupting their function as the site for follicles and the production and secretion of estrogen and progesterone, which regulate the menstrual process and women's hormones. This makes ovarian tumors highly dangerous. The purpose of this research is to understand the characteristics of ovarian tumor disease. This study is qualitative descriptive research using the literature study method through a review of literature from previous research journals. The results of this research explain that there are three types of ovarian tumors: benign tumors, borderline tumors, and malignant tumors. These tumors can develop into cancer in advanced stages, spreading to other organs, and their growth often goes unnoticed, earning them the nickname "silent killer." The characteristics of each tumor stage differ, emphasizing the need for exploration in patients affected by ovarian tumors. Based on the conducted research, it is recommended that further studies be conducted on the clinicopathological characteristics of ovarian tumors.